PENGARUH PERUBAHAN TARIF PAJAK PENGHASILAN SEBELUM DAN SESUDAH BERLAKUNYA UU NO. 36 TAHUN 2008 TERHADAP MANAJEMEN LABA (STUDI EMPIRIS PADA PERUSAHAAN PROPERTY DAN REAL ESTATE DI BURSA EFEK INDONESIA) - Radiman .; Melisa . (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2014)
This study aims to demonstrate and analyze whether or not the effect of net income to earnings management before and after the enactment of the tax rate no. 36 in 2008. Population in this study is the property and real estate company listed on the BEI in the period 2004-2012. The sampling technique using purposive sampling technique. The samples used were 15 companies that meet the sampling criteria. Analysis using different test statistical parametric paired sample t-test with SPSS 16. Results of this study indicate that there are differences in net income before and after the change in tax rates Act of 2008. Conclusion change Act of 2008 tax rates affect earnings management of aspects of net income. Amendment Act of 2008 tax rates negatively affect earnings management. This is evident from the results of the t test is negative, which means with a change in tax rates Act of 2008, the company will minimize profits to reduce tax payments.